2018
DOI: 10.3906/kim-1705-25
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of heteroaryl substituted $\gamma$-lactams from nitrovinyl arenes

Abstract: Abstract:Aliphatic nitroalkanes with different functional groups were synthesized from the Michael addition reactions of active methylene compounds 2 and nitrovinyl arenes 1 in high yields. The synthesized Michael adducts were subjected to intramolecular cyclization to give heteroaryl substituted γ -lactams in good to high yields under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This methodology allows one to obtain the desired products 265 in moderate yields (60−65%) from Michael adducts 264, which were synthesized from active methylene compounds such as methyl-2-(diethylphosphono)acetate ( 262) and nitrovinylarenes 263 in the presence of LiClO 4 and Et 3 N (Scheme 54). 175 The γ-lactams derived from nitrovinyl-thiophene and -furan were tested against several cancer cells and showed that the furan derivative has a higher cytotoxic effect toward human breast cancer (MCF-7) and prostate cancer (PC3) at concentrations of 5 and 6 mM, respectively, compared to the thiophenyl pyrrolidinone. 176 Palacios' research group developed a diastereoselective synthesis of phosphonylated γ-lactams 272 by a cyclization of fluorinated β-aminophosphonates 271 with NaH in THF (Scheme 55).…”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
“…This methodology allows one to obtain the desired products 265 in moderate yields (60−65%) from Michael adducts 264, which were synthesized from active methylene compounds such as methyl-2-(diethylphosphono)acetate ( 262) and nitrovinylarenes 263 in the presence of LiClO 4 and Et 3 N (Scheme 54). 175 The γ-lactams derived from nitrovinyl-thiophene and -furan were tested against several cancer cells and showed that the furan derivative has a higher cytotoxic effect toward human breast cancer (MCF-7) and prostate cancer (PC3) at concentrations of 5 and 6 mM, respectively, compared to the thiophenyl pyrrolidinone. 176 Palacios' research group developed a diastereoselective synthesis of phosphonylated γ-lactams 272 by a cyclization of fluorinated β-aminophosphonates 271 with NaH in THF (Scheme 55).…”
Section: Five-membered Rings: Nonaromatic Aromatic and Benzo-fused He...mentioning
confidence: 99%
“…Fonte -Adaptado de Baron, 2011 Estes compostos atraíram a atenção das indústrias farmacêuticas e dos pesquisadores, com interesse em estabelecer novas metodologias para acesso aos compostos do tipo lactâmicos, devido a sua estrutura singular e consideráveis atividades biológicas como ação anti-inflamatória e antibacteriana na medicina. Além disso, os lactâmicos são intermediários úteis na síntese total de muitos compostos não peptídicos biologicamente ativos (AMABILI et al, 2016;ÇINAR;ÜNALEROGLU, 2018;TAKAO;AOKI;TADANO, 2007).…”
Section: Lactamasunclassified